Bioactive Compounds, Free Radical Scavenging Activity and Xanthine Oxidase Inhibitory Activity from Local Pigmented Rice Extracts of Loei Province - Misuna, Suwatchai; Dedchaisong, Oranish; Ratchamee, Pimonmart; Phooklung, Somruedee; Srichana, Niramol (Naresuan University Journal: Science and Technology (NUJST), 2021)
Pigments in pigmented rice are usually in the pericarp or the seed coat. The color of the seed coat varies from black, purple, red or brown. Pigmented rice contains a range of bioactive compounds including phenolic acids, flavonoids and anthocyanins . This study investigates the free radical scavenging activity and evaluates xanthine oxidase inhibitory activity of the phenolic compound, flavonoid compound and anthocyanin from local pigmented rice extract of Loei province. Khao Pae Daeng, Khao Daeng Mueang Loei, Khao Jao Dam, Khao Niaw Kam, Khao Kam Poon and Khao Dam Leum Pua were extracted with absolute ethanol for phenolic compound and flavonoid compound analysis. Whereas, 1% of hydrochloric acid diluted in methanol is generally used to extract anthocyanin. Total phenolic, total flavonoid and total anthocyanin were analyzed by spectrophotometric method. High-performance liquid chromatography technique was used to identify and quantify phenolic acid, flavonoid and anthocyanin in local pigmented rice extract. Furthermore, the extracts were evaluated for their free radical scavenging activity using DPPH radical and ABTS radical as a substrate and xanthine oxidase inhibitory activity. The extract from Khao Dam Leum Pua showed both maxima of total phenolic contents (88.32±6.03 mgGAE/100g) and total flavonoid contents (364.19±7.12 mgQE/100g). Five phenolic acids were detected in all extract but found in different quantities. Khao Dam Leum Pua, Khao Niaw Kam and Khao Kam Poon was containing greater phenolic acid contents when compared with the other local pigmented rice ( p<0 . 05 ). Likewise, the extract from Khao Dam Leum Pua and Khao Kam Poon showed the maximum of quercetin contents (0.44-0.45 mg/100g). The most of total anthocyanin contents were found in Khao Dam Leum Pua and Khao Kam Poon ( p<0 . 05 ). Khao Dam Leum Pua contained greater cyanidin-3-glucoside (60.03±3.88 mg/100g) and cyanidin contents (16.43±0.93 mg/100g) when compared with the other extract ( p<0 . 05 ). Finally, the extract from Khao Dam Leum Pua displayed the strongest DPPH radical anion scavenging activity (IC 50 =49.78±3.57 µg/ml). Also, the strongest ABTS radical cation scavenging activity was found in Khao Dam Leum Pua (IC 50 =16.54±1.06 µg/ml). The extract from Khao Dam Leum Pua exhibited the strongest xanthine oxidase inhibitory activity with IC 50 values of 64.16±4.42 µg/ml. Significant positive correlations (r 2 ) demonstrate that the free radical scavenging effects of local pigmented rice extract might generally be considered a result of the presence of the phenolic compounds (0.7278) flavonoid compounds (0.6591) and anthocyanin (0.8459). Similarly, correlation analysis showed that anthocyanin such as cyanidin was positively correlated to xanthine oxidase inhibitory activity (0.9192). This study provides new insights into the potential use of local pigmented rice extracts, especially black rice such as Khao Dam Leum Pua and Khao Kam Poon as a source of antioxidants and xanthine oxidase inhibitor. Keywords: bioactive compounds, free radical scavenging activity, xanthine oxidase inhibitory activity, local pigmented rice, Oryza sativa L.